Reprogramming of the circadian clock by nutritional challenge - Eckel-Mahan, Kristin L; Patel, Vishal R; de Mateo, Sara; Orozco-Solis, Ricardo; Ceglia, Nicholas J; Sahar, Saurabh; Dilag-Penilla, Sherry A; Dyar, Kenneth A; Baldi, Pierre; Sassone-Corsi, Paolo (Cell, 2013)
Circadian rhythms and cellular metabolism are intimately linked. Here, we reveal that a high-fat diet (HFD) generates a profound reorganization of specific metabolic pathways, leading to widespread remodeling of the liver clock. Strikingly, in addition to disrupting the normal circadian cycle, HFD causes an unexpectedly large-scale genesis of de novo oscillating transcripts, resulting in reorganization of the coordinated oscillations between coherent transcripts and metabolites. The mechanisms underlying this reprogramming involve both the impairment of CLOCK:BMAL1 chromatin recruitment and a pronounced cyclic activation of surrogate pathways through the transcriptional regulator PPARγ. Finally, we demonstrate that it is specifically the nutritional challenge, and not the development of obesity, that causes the reprogramming of the clock and that the effects of the diet on the clock are reversible.